New York City Taxis in an Uber World - Mammen, Kristin; Shim, Hyoung Suk (Journal of Marketing Development and Competitiveness, 2018)
We empirically examine the effect of Uber’s presence on the demand for medallion taxi trips in New York City. We estimate the percent change in number of Yellow and Green cab trips given a one percent change in number of Uber rides – the elasticity - using rainfall as an instrumental variable. Citywide, Uber rides supplement, rather than replace, Yellow and Green cab rides. For Yellow cabs, this result is powered by the area of Manhattan below 110th street; however during the morning rush only, Uber rides replace Yellow cab rides there. These results suggests Uber competition will have quite different effects in markets depending upon the thickness and vigor of the existing taxi market, and site-specific commuting patterns